A study on efforts in building resilient community towards flood in Pasir Puteh, Kelantan - Siti Nor Aishah, Yusoff (2018)
Malaysia is one of the well- known country that commonly contribute to the natural disaster which is flood. Due to the flood, there are great devastation has occurred as community loss their homes and also other infrastructures. The huge impacts due to flood indicates that the urgent need to increase community’s resilience as during flood of 2014, villagers do not have much experience in protecting themselves from such disasters and for that reason, it is quite likely they suffer quite a lot. Since the villagers were fully unprepared to face the flood, they panicked in witnessing the rising water levels. They did not store food nor did they arrange any other primary aid to meet the immediate needs. Furthermore, their miseries were compounded when relief and other support were delayed due to high levels of water. Their miseries continued even after the floods had subsided as they had very limited options to start life anew. The objectives of this study are to recognize the influencing factors of community to be more resilient towards flood in Pasir Puteh, Kelantan; to identify NGO efforts to build resilient community towards flood in Pasir Puteh, Kelantan; and to determine community in Pasir Puteh, Kelantan participation in mitigation, preparedness, response, and recovery activities to build resilient community towards flood respectively. Mixed methods of collecting and analyzing data using both quantitative and qualitative approaches were used. They provided a comprehensive way of gathering information from households and non-governmental organization (NGO). The data were analyzed and the results assessed through the lens of the overarching concept of community resilience that encompasses six types of resilience. This new approach provided a holistic perspective in exploring factors that influence the building of community resilience. Findings from this study revealed evidence that a number of factors that were gradually increasing their level of resilience. In order to achieve preparedness, response, recovery and also community resilience, the various types of resilience needed to be reinforced. Other than that, findings from this study showed evidence that NGO’s effort gave significant contributions in building resilience community as there were many assistance given to community and also their brilliant planning for long-term assistance. It was found that social networking and a combination of local knowledge with that of experts, through community participation in decision making, were crucial in reinforcing community resilience. Based on the research findings, disaster resilience was everyone’s business and was a shared responsibility among communities, the private sector, and government. Community leaders and government officials face decisions every day that may pit short-term interests against longer-term goals. Increasing resilience to disasters will require decisions and actions that are informed and forward-looking. Although disasters will continue to occur, actions that move the nation from a reactive to a proactive approach will reduce many of the societal and economic burdens and impacts that disasters cause. Building the nation’s resilience was a long-term process, one that will be socially and politically challenging, but the reward for our efforts will be a safer, healthier, more secure, and more prosperous nation.